PENDAMPINGAN DIGITAL UNTUK MTS MIFTAHUL ULUM PASANGGAR MELALUI PEMBUATAN WEBSET PROFIL - Ali, Ibnu (BAJHRAH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Current cultural changes are reflected in the increasingly widespread use of the internet globally. The internet has become an important necessity as a medium for delivering global information. The benefits of the internet are mainly felt in various fields such as business, entertainment and education. However, Madrasah Tsanawiyah Miftahul Ulum Pasanggar still uses a simple method of conveying information, namely through notice boards. Limitations in this method result in the information conveyed being limited. To overcome this problem, it is necessary to create a profile website for Madrasah Tsanawiyah Miftahul Ulum Pasanggar. It is hoped that this website will make it easier for students, teachers, academic staff, parents and the general public to obtain information related to the school. The focus of this research is the creation of a website that describes the profile of Madrasah Tsanawiyah Miftahul Ulum Pasanggar. The research methods used include observation, interviews, literature study, analysis, design, manufacture, testing and implementation. With the Madrasah Tsanawiyah Miftahul Ulum Pasanggar profile website, it is hoped that the public can easily find information about the school. This will increase the accessibility of information and expand the range of information that can be obtained by the public regarding the profile of Tsanawiyah Miftahul Ulum Pasanggar Pegantenan Pamekasan.